2010
DOI: 10.1007/s13206-010-4109-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of rat liver proteins differentially induced by trichloroethylene

Abstract: Trichloroethylene (TCE), a volatile and lipophilic solvent widely used in industrial degreasing applications, is believed to be toxic in humans. To identify possible protein biomarkers of early TCE-induced hepatotoxicity, we treated rats with a single dose of TCE equivalent to 10% of LD 50 and analyzed their liver proteomes 72 h after dosing. We identified eight liver proteins that exhibited a TCE-induced change in expression level of at least 2-fold; three of these proteins were upregulated and the rest were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…After isoelectric focusing, the strips were soaked twice for 20 min each in equilibration buffer (6 M urea, 2% w/v SDS, 20% v/v glycerol, 5 mM tributylphosphine, 2.5% acrylamide, 0.01% bromophenol blue, 0.375 M Tris-HCl, pH 8.8). The seconddimension SDS-PAGE was performed in 8Á16% gradient polyacrylamide gels without a stacking gel, at 108C for 2 h at 5 mA/gel and then at 18 mA/gel (Bartkowiak et al 2009;Choi et al 2009;Jeon et al 2011;Park et al 2010). Protein bands were visualized by staining with Coomassie Brilliant Blue G-250.…”
Section: Two-dimensional Gel Electrophoresis (2-de)mentioning
confidence: 99%
“…After isoelectric focusing, the strips were soaked twice for 20 min each in equilibration buffer (6 M urea, 2% w/v SDS, 20% v/v glycerol, 5 mM tributylphosphine, 2.5% acrylamide, 0.01% bromophenol blue, 0.375 M Tris-HCl, pH 8.8). The seconddimension SDS-PAGE was performed in 8Á16% gradient polyacrylamide gels without a stacking gel, at 108C for 2 h at 5 mA/gel and then at 18 mA/gel (Bartkowiak et al 2009;Choi et al 2009;Jeon et al 2011;Park et al 2010). Protein bands were visualized by staining with Coomassie Brilliant Blue G-250.…”
Section: Two-dimensional Gel Electrophoresis (2-de)mentioning
confidence: 99%
“…Expression of the alpha-2u globulin gene was also changed under oxidative stress to affect developmental and multihormonal regulation 28 . Expression of the alpha2u globulin was also down-regulated in rat liver exposed to trichloroethylene (TCE) 29 .…”
Section: Proteomic Analysis Of Differentially Expressed Proteins By Ementioning
confidence: 99%
“…To get total protein, the liver tissue was removed through a midline abdominal incision, frozen in liquid nitrogen and stored until analysis 29 .…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH toxicity is quite structurally dependent on isomers 7 Gene expression profiling studies on VOCs and PAHs have been reported 10,11 . Proteomic tools such as two-dimensional gel electrophoresis (2D-GE) and mass spectrometry analysis have been applied for the analysis of rat livers 12,13 .…”
Section: Introductionmentioning
confidence: 99%